2019
DOI: 10.1111/nph.16077
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 knockout of leghemoglobin genes in Lotus japonicus uncovers their synergistic roles in symbiotic nitrogen fixation

Abstract: Summary Legume nodules contain high concentrations of leghemoglobins (Lbs) encoded by several genes. The reason for this multiplicity is unknown. CRISPR/Cas9 technology was used to generate stable mutants of the three Lbs of Lotus japonicus. The phenotypes were characterized at the physiological, biochemical and molecular levels. Nodules of the triple mutants were examined by electron microscopy and subjected to RNA‐sequencing (RNA‐seq) analysis. Complementation studies revealed that Lbs function synergistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 72 publications
0
84
2
Order By: Relevance
“…Leghemoglobins are essential for buffering oxygen in nodules at low levels while transporting it rapidly to rhizobia. RNAi and CRISPR/Cas9 of LjLB1, LjLB2, and LjLB3 resulted in nodules with elevated oxygen concentrations but reduced ATP:ADP ratios and defective SNF (Ott et al, 2005;Wang et al, 2019). Importantly, nif genes (nifH) were not induced in these nodules (Ott et al, 2009).…”
Section: Activation Of Bacterial Nitrogenasementioning
confidence: 99%
“…Leghemoglobins are essential for buffering oxygen in nodules at low levels while transporting it rapidly to rhizobia. RNAi and CRISPR/Cas9 of LjLB1, LjLB2, and LjLB3 resulted in nodules with elevated oxygen concentrations but reduced ATP:ADP ratios and defective SNF (Ott et al, 2005;Wang et al, 2019). Importantly, nif genes (nifH) were not induced in these nodules (Ott et al, 2009).…”
Section: Activation Of Bacterial Nitrogenasementioning
confidence: 99%
“…The mutant nodules showed an increase in the internal free O 2 concentration and alterations in the expression of many genes, including bacterial nif and fix (Ott et al , ). Subsequent work using CRISPR/Cas9 to obtain single, double and triple ( lb123 ) mutants concluded that the three Lbs act additively to maintain optimal N 2 fixation (Wang et al , ). This study also provided RNA‐sequencing information of c. 20 000 genes of the lb123 nodules.…”
Section: Globins In Symbiosismentioning
confidence: 99%
“…This study also provided RNA‐sequencing information of c. 20 000 genes of the lb123 nodules. These Lb‐free nodules showed cell vacuolization, accumulation of poly‐β‐hydroxybutyrate, disruption of mitochondria and enhanced concentrations of superoxide and peroxide (Wang et al , ).…”
Section: Globins In Symbiosismentioning
confidence: 99%
“…With the advent of newer technologies like genome editing, manipulating genome structures has become easier. Genome editing tools like CRISPR/Cas9 were employed to knockout leghemoglobin (Lbs) genes in L. japonicus, and uncovered their synergistic roles in symbiotic nitrogen fixation [128]. This study concluded that Lbs acts additively in nodules and the lack of Lbs results in early nodule senescence.…”
Section: Application Of Transgenic Approaches and Genome Editingmentioning
confidence: 99%
“…This study concluded that Lbs acts additively in nodules and the lack of Lbs results in early nodule senescence. It also provided insight into the reprogramming of the gene expression network in the absence of Lbs, probably as a result of an uncontrolled free O 2 concentration [128]. Various genomics approaches and biotechnology efforts in this direction will help us to learn more about the molecular basis of nodulation at the genomic/proteomic/metabolomic level, which would effectively translate into major gains in research and contribute to more sustainable agriculture (Figure 4).…”
Section: Application Of Transgenic Approaches and Genome Editingmentioning
confidence: 99%